2019
DOI: 10.1152/ajprenal.00350.2019
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial effects on electrolyte homeostasis in the kidney

Abstract: Insulin is known to be an important regulator of a number of different channels and transporters in the kidney, but its role in the kidney to prevent Na+ and volume loss during the osmotic load after a meal has only recently been validated. With increasing numbers of people suffering from diabetes and hypertension, furthering our understanding of insulin signaling and renal Na+ handling in both normal and diseased states is essential for improving patient treatments and outcomes. The present review is focused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…Insulin-clamp studies, maintaining a stable filtered load of glucose, suggest an independent effect of insulin, likely enhancing post-prandial sodium retention at the diluting segment of the distal nephron (18). Indeed, recent reports have shown that insulin exerts a RAAS-independent post-prandial reclamation of water and sodium, likely mediated by a significant increase in the open probability of ENaC along collecting tubules (19). Additionally, insulin also directly stimulates SGLT2 expression, as illustrated in studies using renal tubule-specific insulin receptor knockout (KO) mice (20).…”
Section: Discussionmentioning
confidence: 99%
“…Insulin-clamp studies, maintaining a stable filtered load of glucose, suggest an independent effect of insulin, likely enhancing post-prandial sodium retention at the diluting segment of the distal nephron (18). Indeed, recent reports have shown that insulin exerts a RAAS-independent post-prandial reclamation of water and sodium, likely mediated by a significant increase in the open probability of ENaC along collecting tubules (19). Additionally, insulin also directly stimulates SGLT2 expression, as illustrated in studies using renal tubule-specific insulin receptor knockout (KO) mice (20).…”
Section: Discussionmentioning
confidence: 99%
“…Electrolytes are pivotal elements for cell signaling [ 174 ], homeostasis [ 175 ], and kidney function [ 176 ]. They also play a vital role in the regulation of CDs, such as cardiovascular diseases.…”
Section: Applications Of Mns In the Detection Of CD Biomarkersmentioning
confidence: 99%